PENERAPAN MANAJEMEN TERPADU BALITA SAKIT (MTBS) DI PUSKESMAS KOTA GORONTALO - Andi Akifa Sudirman; Lenny Ali (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Integrated Management of Childhood Illness (IMCI) is a health service strategy aimed at reducing mortality and morbidity. This research was conducted at Health Center Kota Gorontalo. The purpose of this study To determine the implementation of Integrated Management of Childhood Illness (IMCI) at the Health Center of Gorontalo City. This research method is a qualitative approach that aims to know clearly and more deeply about the application of IMCI in Health Center in Gorontalo City. The results showed that viewed from human resources, all Health Center already have officer of IMCI even in all Health Center besides in charge of IMCI there are also other officers who have been trained. Of 10 health centers, 6 health centers have implemented IMCI, 3 Health Center have not implemented IMCI, and there is 1 Health Center implementing IMCI to some babies. Then 3 Health Center that do not have IMCI form, 4 Health Center do not have IMCI clinics, 2 Health Center which do not have mother's advice card and 4 Health Center which do not have budget for IMCI.